Effects of clay types and fractions on elastic properties of artificial clay-bearing sandstones: an experimental study. (18th January 2023) - Li, Kuizhou; Han, Xuehui; Zhang, Hao; Fang, Tao; Luo, Xingping; Nie, Junguang
Abstract: Experimentally understanding the effects of clay type and fraction on the elastic properties of clay-bearing sandstone is crucial for exploring hydrocarbon reservoirs. Therefore, we artificially synthesized a series of pure clay rocks and clay-bearing sandstones with different clay types and fractions, and conducted the ultrasonic measurements to investigate the elastic behaviors. According to experiments on pure clay rocks, illite rocks have the highest porosity, followed by montmorillonite rocks and chlorite rocks. In terms of elastic properties, illite rocks show the highest ultrasonic P- and S-wave velocities, followed by chlorite rocks and montmorillonite rocks. For clay-bearing sandstones, the measured results indicate that clay types and fractions significantly influence both the physical and elastic properties. Specifically, the porosity of chlorite-bearing sandstone is systematically lower than that of illite-bearing and montmorillonite-bearing sandstone. The chlorite-bearing sandstone has the highest P- and S-wave velocities, followed by illite-bearing and montmorillonite-bearing sandstone. Moreover, the clay fraction also affects porosity–velocity trends. The porosity first falls and then increases as the clay fraction rises, while the P- and S-wave velocities first rise and then fall and, in turn the turning point occurs at the ∼30% clay fraction. The potential mechanism of the turning point is analyzed based on the microscopic distribution of clay and sandstone. Additionally, the clay fraction and distribution also affect the electrical conductivity and permeability of the clay-bearing sandstone, implies that the clay types, clay fraction and clay distribution are non-negligible factors in reservoir evaluation.